2018
DOI: 10.1063/1.5037076
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer strain effects on the structural behavior of BiFeO3/LaFeO3 superlattices

Abstract: Artificial (BiFeO3)0.5 /(LaFeO3)0.5 superlattices (SLs) have been grown by pulsed laser deposition. The periodicity was varied from 150 Å to 25 Å and the relative ratio between BFO and LFO is kept constant in each period. X-ray diffraction, transmission electron microscopy (TEM) and Raman spectroscopy investigations indicate antiferroelectric-like structures for large periodicity ( ≥76 Å) while Pnma LaFeO3-like structures are observed for small periodicity ≤50 Å. Room temperature Magnetic measurements were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In superlattices of ferroelectric BiFeO 3 and paraelectric LaFeO 3 , a region of complex/ mixed-phase BiFeO 3 has been found for intermediate superlattice layers and attributed to a nanoscale twinned phase (23). In other superlattices of BiFeO 3 and LaFeO 3 , a PbZrO 3 -like antipolar BiFeO 3 phase has been identified and attributed to result from symmetry mismatch and strain (24,25). This is corroborated by additional DFT calculations showing that antiferroelectric phases can be induced from ferroelectrics as a result of interfacial charge (26) and related experimental work on short-period ferroelectric superlattices with confining dielectric layers (2) and short-period antiferroelectrics (27).…”
Section: Introductionmentioning
confidence: 99%
“…In superlattices of ferroelectric BiFeO 3 and paraelectric LaFeO 3 , a region of complex/ mixed-phase BiFeO 3 has been found for intermediate superlattice layers and attributed to a nanoscale twinned phase (23). In other superlattices of BiFeO 3 and LaFeO 3 , a PbZrO 3 -like antipolar BiFeO 3 phase has been identified and attributed to result from symmetry mismatch and strain (24,25). This is corroborated by additional DFT calculations showing that antiferroelectric phases can be induced from ferroelectrics as a result of interfacial charge (26) and related experimental work on short-period ferroelectric superlattices with confining dielectric layers (2) and short-period antiferroelectrics (27).…”
Section: Introductionmentioning
confidence: 99%
“…The microscope was equipped with a spherical aberration correction (Cs) system and a contrast diaphragm of 60 μm. These regularly spaced satellite peaks are proof of a periodic chemical modulation along the out-of-plane growth direction [19]. It is not possible to assign a peculiar diffraction peak for BFO layers and one for the NFO layers.…”
Section: Methodsmentioning
confidence: 93%
“…Artificially modulated heterostructures such as superlattices (SLs) are also employed to better understand the competing interactions that exist within the MPB. For instance, BiFeO3/ LaFeO3 (BFO/LFO) SLs deposited on different substrates have been studied by different groups [17][18][19][20][21]. Interestingly, a strain-and symmetry-mismatch-induced stabilization of the AFE-like state was reported in BFO/LFO SLs [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3d). For example, in superlattices and heterostructures of BiFeO 3 with centrosymmetric P nma LaFeO 3 , BiFeO 3 has been reported to adopt the antiferroelectric PbZrO 3 structure [57,58], or even observed in an entirely new antiferroelectric structure, which has not been reported in the bulk [15]. Density functional calculations indicated that, for the strain conditions of the sample, this antiferroelectric phase is only slightly higher in energy than the ground-state polar phase, and it is favored because of its lower electrostatic energy cost [15].…”
Section: Interfaces Of Bismuth Ferrite With Insulating Centrosymmetri...mentioning
confidence: 99%